2015
DOI: 10.1177/1753193415618391
|View full text |Cite
|
Sign up to set email alerts
|

Histological assessment of the triangular fibrocartilage complex

Abstract: The morphological structure of the seven components of triangular fibrocartilage complexes of 11 cadaver wrists of elderly people was assessed microscopically, after staining with Hematoxylin-Eosin and Elastica van Gieson. The articular disc consisted of tight interlaced fibrocartilage without blood vessels except in its ulnar part. Volar and dorsal radioulnar ligaments showed densely parallel collagen bundles. The subsheath of the extensor carpi ulnaris muscle, the ulnotriquetral and ulnolunate ligament showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 19 publications
1
48
0
Order By: Relevance
“…tached to the styloid process via chondral-apophyseal entheses, with gradual changes from the dorsal in the middle third of the styloid process, to the palmar direction in the distal third. These results are supported bySemisch et al (2016), who reported thatF I G U R E 5In vivo MR imaging of the attachment of the radioulnar ligaments on the styloid process in younger and healthy participants. Locations of the slices are indicated as blue lines (a).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…tached to the styloid process via chondral-apophyseal entheses, with gradual changes from the dorsal in the middle third of the styloid process, to the palmar direction in the distal third. These results are supported bySemisch et al (2016), who reported thatF I G U R E 5In vivo MR imaging of the attachment of the radioulnar ligaments on the styloid process in younger and healthy participants. Locations of the slices are indicated as blue lines (a).…”
supporting
confidence: 73%
“…Moreover, because previous anatomical studies included either aged cadavers (af Ekenstam and Hagert, 1985;Nakamura and Makita, 2000;Nakamura et al, 1996;Nakamura et al, 2001;Semisch et al, 2016) or specimens in which the age is unknown (Ishii et al, 1998;Palmer and Werner, 1981), these anatomical findings might not reflect the morphological features of younger and healthy specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Both retinacula showed dense and regular fibrous tissue, with tightly packed, unidirectional and parallel arrangements of collagen fibers (Semisch et al. ). In addition, the retinacula were surrounded by loose conjunctive tissue and blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…The study of LaPorte et al (2014) into the triangular fibrocartilage complex (Semisch et al, 2016) revealed further contributing nerve stems for this structure’s sensory innervation pattern. A limitation of our study is that we did not dissect possible articular branches of other adjacent nerves.…”
Section: Discussionmentioning
confidence: 99%